American Society of Missiology 2025 Lifetime Achievement Award Recipient: Response - Lewis, Bonnie Sue (Missiology, 2026)
Gratitude for the honor of receiving the prestigious Lifetime Achievement Award of the American Society of Missiology for 2025.